y=f(xy^2)
y'=f'(xy^2)*(xy^2)
=f'(xy^2)*2xy
=2xyf'(xy^2)
第二个求导你好像错了
y=f(x+y,y^2)
y'=f'1(x+y,y^2)*(x+y)' +f'2(x+y,y^2)*(y^2)'
=f'1(x+y,y^2)*1 +f'2(x+y,y^2)*2y
=f'1(x+y,y^2)+2yf'2(x+y,y^2)u=f(ty/x,t^2+x/y)x=g(t)y=w(t)你求下这个,,不明白u=f(ty/x,t^2+x/y)表达式的准确表达式ty/x是x分之tyt^2+x/y 还是(t^2+x)y还有求什么?u=f(ty/x,t^2+x/y)du/dt=f'1(ty/x,t^2+x/y)*(ty/x)'+f'2(ty/x,t^2+x/y)*(t^2+x/y)' =f'1(ty/x,t^2+x/y)*[(ty)'x-(ty)x']/x^2+f'2(ty/x,t^2+x/y)*[2t+(x'y-xy')/y^2]=f'1(ty/x,t^2+x/y)*(yx+ty'x-tyx')/x^2+f'2(ty/x,t^2+x/y)*[2t+(x'y-xy')/y^2]太复杂了,不知对不对。